IMPACT OF DIETARY REPLACEMENT OF INORGANIC ZINC WITH ORGANIC ZINC ON OVARIAN FOLLICULOGENESIS - NAGALAKSHMI, D; SADASIVA RAO, K; ARUNA KUMARI, G; SRIDHAR, K (The Indian Journal of Animal Reproduction, 2017)
Seventy-two weaned Sprague Dawley female rats (98.4±1.5 g) were randomly distributed to four dietary groups with six replicates in each and reared in polypropylene cages for 14 weeks. Dietary treatments were prepared by adding 12 ppm Zn to the basal diet (formulated with purified ingredients without Zn) from inorganic source (ZnCO3, control) and replacing inorganic Zn (Zni) at 0% (100i), 50% (50i:50o), 75% (25i:75o) and 100% (100o) with organic Zn (Zno, Zn methionine). All the rats were sacrificed at the end to collect the ovaries and the liver to study ovarian folliculogenesis and thiobarbituric acid reacting substances (TBARS), respectively. The dietary incorporation of Zno irrespective of level of replacement of Zni lowered (p<0.05) TBARS in liver. The highest (p<0.05) ovarian weight was observed after feeding 100% Zno compared to 100% Zni and other Zn combinations. Serum progesterone (on 70th d) was increased (p<0.05) after Zno supplementation compared to sole Zni supplementation. The regular estrus cycle was observed following Zno supplementation at either combination, while 30% Zni supplemented rats had irregular estrus cycle. The number of preantral follicles in ovaries were comparable (p>0.05) among the dietary groups, while the percentage of graafian follicles and corpus luteum was though comparable, the number improved by 53.2% and 26.7% with 75% replacement and, 60% and 65.14% with 100% replacement of Zni with Zno, respectively. In brief, Zno replacing 75% or 100% of Zni improved the follicular development and its maturation in ovaries of rats.